Studies on the effects of chemical preservatives on the quality of strawberry (Fragaria ananassa) juice in Bangladesh - Sabina, R; Miyan, SH; Hoque, MM (International Journal of Natural Sciences, 2012)
This study was carried out to assess the nutritive value of fresh strawberry (Fragaria ananassa) juice and to observe the effect of chemical preservatives on the acidity, ascorbic acid and total soluble solids (TSS) content of strawberry juice. Strawberry was being collected from the local farm of Sylhet city. The proximate composition of strawberry juice was found to have contents of moisture 89.64%, fat 0.48%, fiber 1.013%, ash 0.53%, Titrable acidity 1.02%, ascorbic acid 120 mg/100g, TSS 6%, and pH 3.7. To observe the effects of chemical preservatives the samples were treated with 30% sucrose, 0.2% sodium benzoate, 0.2% potassium sorbet, mixture of 30% sucrose and 0.2% sodium benzoate, mixture of 30% sucrose and 0.2% potassium sorbet, mixture of 30% sucrose, 0.2% sodium benzoate and 0.2% potassium sorbet. The study was conducted for 3 months; storage on refrigeration temperature and the content of acidity; ascorbic acid and TSS were assessing every 15th day’s interval. The result showed mixture of 30% sucrose, 0.2% sodium benzoate and 0.2% potassium sorbet gives retention to most of the nutrients during 3 months storage. The results showed that the ascorbic acid of the juice was found to be with minimum percentage decrease in sample T6 (6.93%) and maximum in T0 (64.69), on acidity of juice there was no such significant changes thus showing similar mean values in the samples, and TSS of juice recorded maximum mean value in T6 (33.5) and minimum mean value T0 (5.1) where maximum increase was observed in T0 (20%) and minimum in T5 (3.54). The results suggested that the effects of chemical preservatives have significant role in strawberry juice and its livelihood. The changes of ascorbic acid content of strawberry juice for T0 treatment significantly changes with T3 (p=.025), T4 (p=.029), T5 (p=.027), T6 (p=.001).The changes of acidity treated with different preservatives significantly changes with period of time but insignificantly changes with the treatment. The changes of TSS content of strawberry juice significantly changes with treatment. The homogeneous subsets are T0 T2 T4 and the subsets b contain T3, T1, T5 and T6 (p=o.ooo). Among all the treatments T6 were most effective in maintaining the nutritional quality during storage. DOI: http://dx.doi.org/10.3329/ijns.v1i4.9736 IJNS 2011 1(4): 97-101